2017
DOI: 10.3389/fimmu.2017.00663
|View full text |Cite
|
Sign up to set email alerts
|

Induced Regulatory T Cells Superimpose Their Suppressive Capacity with Effector T Cells in Lymph Nodes via Antigen-Specific S1p1-Dependent Egress Blockage

Abstract: Regulatory T cells (Tregs) restrict overexuberant lymphocyte activation. While close proximity between Tregs and their suppression targets is important for optimal inhibition, and literature indicates that draining lymph nodes (LNs) may serve as a prime location for the suppression, signaling details orchestrating this event are not fully characterized. Using a protocol to enable peripheral generation of inducible antigen-specific Tregs (asTregs) to control allergen-induced asthma, we have identified an antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In reality, many of the suppressive mechanisms applicable for CD4 þ T cells may also be at work for CD8 þ T cells. In our previous work, we reported that in an asthma model, peripherally induced Tregs by a vaccine regimen blocked CD4 þ T-cell function via surface downregulation of S1P1 (32). In this report, we found that a similar regulation of CD8 þ T cells: Tregs migrating into TDLNs from the tumor downregulated S1P1 expression on these cells.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In reality, many of the suppressive mechanisms applicable for CD4 þ T cells may also be at work for CD8 þ T cells. In our previous work, we reported that in an asthma model, peripherally induced Tregs by a vaccine regimen blocked CD4 þ T-cell function via surface downregulation of S1P1 (32). In this report, we found that a similar regulation of CD8 þ T cells: Tregs migrating into TDLNs from the tumor downregulated S1P1 expression on these cells.…”
Section: Discussionmentioning
confidence: 50%
“…Treg migration to these sites may be a key step for easy access to this cytokine (31). However, more and more reports indicate that lymphoid tissues are an important, if not the key, location for Tregs to mediate their suppression (19,32).…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in S1PR1 expression in T cells could therefore limit the capacity of adoptively transferred cells to exit the LN they infiltrated. Furthermore, it has also been described that antigen-specific regulatory T cells exert their immunosuppressive action in the LNs by promoting, among other things, a decrease in the expression of S1P1R in effector T cells, thereby trapping these cells in the LN [180]. Evaluating the expression of S1PR1 and of other chemokine receptors, such as CCR7 [181], that control T cell migration in adoptively transferred cells would therefore be useful to optimize the migratory profile of transferred MNP-loaded T cells, so that their retention in the tumor is not only promoted by the EMF but also by biological factors such as chemokines.…”
Section: In Vivo Magnetic Tumor Targeting Of Lymphoid Cells: Not So Smentioning
confidence: 99%
“…Activation of antigen-specific T cell response is critical for the treatment of cancer and viral diseases [18][19][20][21]. The activated antigen specific effector T cells could migrate into inflammation or tumor deposits through lymph node [22]. Therefore, modulation of immune response could benefit the treatment of cancer immunotherapy [23].…”
Section: Regulation Of T Cell Activation By Dubsmentioning
confidence: 99%